Interleukin 2- and polyomavirus middle T antigen-induced modification of phosphatidylinositol 3-kinase activity in activated T lymphocytes. - Augustine, J A (1991)
Stimulation of activated T lymphocytes with interleukin 2 (IL-2) results in rapid increases in intracellular protein tyrosine phosphorylation. Both the identity of the protein tyrosine kinase (PTK) activated by IL-2 receptor ligation and the identities of the critical target proteins for this PTK remain largely undefined. In this article, we demonstrate that stimulation of activated murine or human T cells with IL-2 for 10 to 30 min induces two- to threefold increases in the level of phosphatidylinositol (PtdIns) 3-kinase activity present in antiphosphotyrosine (p-Tyr) antibody immunoprecipitates from these cells. Furthermore, substantial levels of PtdIns 3-kinase activity were coprecipitated from IL-2-deprived T cells by antibodies to the src-related PTK p59fyn. Cellular stimulation with IL-2 induced a two- to threefold increase in the level of p59fyn-associated PtdIns 3-kinase activity. To examine the effect of a constitutive increase in PtdIns 3-kinase activity on the growth factor responsiveness of activated T cells, murine CTLL-2 cells were transfected with a polyomavirus middle T antigen (MTAg) expression vector. Anti-p-Tyr and anti-p59fyn immunoprecipitates from MTAg-transfected CTLL-2 cells contained three- to sixfold higher levels of PtdIns 3-kinase activity than wild-type cells. Immune complex kinase assays revealed that MTAg expression concomitantly induced a constitutive threefold increase in the PTK activity of p59fyn in these cells. However, stable MTAg expression did not abrogate the dependence of CTLL-2 cells on exogenous IL-2 for continued growth and proliferation.